Performance of fat snook juveniles reared at different temperatures - Daniel Correia; Luiz Henrique Castro David; Sara Mello Pinho; João Costa-Filho; Maurício Gustavo Coelho Emerenciano; Giovanni Lemos de Mello (Acta Scientiarum. Animal Sciences, 2018)
We aimed at evaluating the effects of different water temperatures on the zootechnical performance of fat snook. The experiment lasted for 60 days, which was conducted in water recirculation systems, and was randomly designed with three treatments and three replicates each, corresponding to three water temperatures (25, 28 and 31°C). A total of 225 fat snook juveniles with a mean weight of 6.45 ± 0.58 g were used, which were fed daily until apparent satiety. Zootechnical parameters were assessed and feeding rates were registered for each tested temperature. Survival rates varied from 96 to 100% among treatments. Higher values of standard and total length, and weight gain were found in 28 and 31°C (p < 0.05). With regard to final weight, final biomass, feed conversion and specific growth rate, no significant differences were observed (p > 0.05). Feeding rates did not differ among evaluated temperatures. The results show that the used temperatures did not negatively affect zootechnical performance of fat snook juveniles.